Preferences of the scholar Sheikh Ma'ruf al-Nawdhi (d. 1254 AH) In his book, "Sullam al-Wusul" (The section on command as an example) - Abdullah, L.Dr. Aram Jalal (Sulaimani Journal for Humanities, 2024)
This study deals with the preferences of the issues related to the topic of the command, by the scholar Sheikh Maarouf Al-Nawdahi, who was born in the city of Sulaymaniyah in the year (1166 AH - 1752 AD) and died there in the year (1254 AH - 1838 AD), as he had a scientific ability in all rational and transmitted sciences, and he was fond of versifying the texts in circulation. Here we talk about one of the most important things he versified in the science of the principles of jurisprudence in his book (Sullam Al-Wusul). The study included an introduction, two sections and a conclusion. The first section: I devoted to the personal and scientific life of the scholar Sheikh Maarouf Al-Nawdahi and the importance of the book Sullam Al-Wusul, and the second section: his preferences in the topic of the command, and as for the conclusion it was in the most important results that I reached in this research.
Keywords: Preferences; Sheikh Maarouf AlNoudhi; The Ladder of Access; The Topic of Command; Principles of Jurisprudence